(untitled) (Raparin Journal of Humanities (RJH), 2025)
The best and most important of the sciences are the sciences related to the words of the Lord of the Servants, Including interpretations and the study of hadiths contained in it, in order to distinguish the correct from the weak The purpose of this research is to study the hadiths in Surah Al-Fatihah, which are authentic Sahihain In the commentary (Hasan al-Bayan in the tafsir of the Qur’an), by Sheikh Mohammed Taha al-Balisani, favor for the interpretation of a great Kurdish scholar Sheikh Mohammed Taha al-Balisani This study is a hadith critical study, in which I tried to write the hadiths mentioned in Surat Al-Fatihah, except for the Sahihain Then the hadiths were included in the four Sunan books if it is not there I got out the information in various other Sunan books. Then I started studying its evidence if with an authentic chain, I contented with mentioning its men and documenting them with the scholars in the books of Al-Jarh and Al-Ta’deel, which collected the sayings of the scholars in it. And if there was a man in her series about whom he differed, or a righteous one, or a weak one, or an unknown person, then he collected the scholars’ sayings about him, and then ruled on him Then I judged its chain of transmission, and then judged the hadeeth with its chain of transmissions. the research reached several results, the most important of which are:1- This interpretation is full of hadiths and narrations.2- It contains authentic, good, and weak hadiths, even fabricated ones. 3- The Sheikh of the interpreter used many verses, hadiths, and narrations in his interpretation.4-The sheikh of the commentator does not care much about studying the hadiths in his interpretation, so he may have mentioned a hadith that he does not mention its chains of narrators and does not speak about it.